2016
DOI: 10.1590/1414-462x201600030199
|View full text |Cite
|
Sign up to set email alerts
|

Exposição ocupacional de trabalhadores rurais a agrotóxicos

Abstract: Resumo Objetivos Avaliar o perfil dos trabalhadores rurais do município de Picos, no Estado do Piauí e suas práticas e atitudes quanto à utilização de agrotóxicos. Métodos A coleta dos dados (n=159) foi realizada em Picos com levantamento de dados socioeconômicos, utilização de equipamentos de proteção individual (EPIs), armazenamento e destino das embalagens de agrotóxicos, toxicidade e risco ambiental. Resultados A maioria dos agricultores era do sexo feminino (63%), não concluiu o ensino fundamental (55,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
37

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 26 publications
2
17
0
37
Order By: Relevance
“…Santana et al 24 reported in their study with farmers that 55.3% had a low level of education and that 24.5% were illiterate, with 64% using pesticides. The low level of education can make it difficult to read and understand the harmful effects of pesticides, but it cannot be considered as an isolated factor for its incorrect use.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Santana et al 24 reported in their study with farmers that 55.3% had a low level of education and that 24.5% were illiterate, with 64% using pesticides. The low level of education can make it difficult to read and understand the harmful effects of pesticides, but it cannot be considered as an isolated factor for its incorrect use.…”
Section: Resultsmentioning
confidence: 94%
“…In the study by Santana et al 24 , farmers who claimed to work with pesticides reported that information on the use of the product, in 44.2%, was obtained through neighbors, as well as through television and radio. A portion said they received guidance from professionals, however, 18.6% never had any information on how to correctly use the pesticide.…”
Section: Ddt (Dichlorodiphenyltrichloroethane)mentioning
confidence: 99%
“…A study showed that workers burned the packaging or discarded it in the environment (landfills, dumps and riverside), and although most read the label, they reported that there were technical terms, lack of clarity in the language and use of very small letters which made it difficult to understand the information contained on the label. 58 Therefore, when identifying the risk factors for the health of these workers, some measures can be developed and adopted aimed at reducing work-related illness, such as investing in scientific research that uses laboratory tests to detect changes in the body, encouragement through public policies to organic agriculture, guidance to workers on safe practices in the application of these products, health education work for the population. However, in order to know the consequences and know how to prevent them, a multi-professional work in health is required, in which professionals report cases of diseases that may be associated with pesticides.…”
Section: Discussionmentioning
confidence: 99%
“…Os impactos do uso de agrotóxicos para a Saúde Pública são amplos, atingem vastos territórios e envolvem diferentes grupos populacionais, como trabalhadores de diversos ramos de atividades (PIGNATI et al, 2017), sendo assim, estão entre os mais importantes fatores de risco à saúde da população geral, especialmente dos trabalhadores rurais que, constantemente, fazem uso de tais produtos. Dependendo da forma, tal utilização pode também trazer consequências para o meio ambiente (SANTANA;MOURA;NOGUEIRA, 2013;ROSSI, 2015). Agrotóxicos são substâncias ou misturas de substâncias usadas tanto na prevenção quanto no controle de uma peste (doença de plantas, insetos, ervas daninhas, roedores, fungos, nematoides, etc.).…”
Section: Introductionunclassified